THE INFLUENCE OF EDUCATION, WELFARE AND RESIDENTIAL AREA ON ADOLESCENT MARRIAGES - Norma Yuni Kartika; Muhammad Efendi; Ellyn Normelani; Heru Heru; Sopyan Sopyan (Universitas Andalas, 2021)
The low median of age of first marriage in South Kalimantan is partly due to the high number of adolescent marriages that hinder the maturity age of marriage program. Adolescent marriages in this study is the age at first marriage for someone under the age of 20 years. This paper aims to analyze the factors that influence adolescent marriage in South Kalimantan. The study used a cross-sectional research design with data from the 2017 Indonesian Demographic and Health Survey (IDHS), South Kalimantan Province. The sample in this study were all married women aged 15-49 years who were respondents to the 2017 IDHS, which were divided into two categories as follows. (1) The category of adolescent marriage was the age of first marriage 15-19 years who met the criteria, amounting to 305 respondents. (2) The category of adult marriage is the age at first marriage of 20 years and over who meets the criteria, amounting to 328 respondents. The analysis in this study used univariable, bivariable and multivariable analysis. The results of the analysis show that 13.3 percent of women with low education, come from poor households and live in rural areas, cause adolescent marriages in South Kalimantan.